PENGARUH USER EXPERIENCE ,PERCEIVED QUALITY DAN PERCEIVED SACRIFICE TERHADAP BEHAVORIAL INTENTION DAN COSTUMER SATISFACTION PADA APLIKASI MOBILE GOJEK DI KOTA PALEMBANG - Efrina Masdaini; Romidon Hidayat (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2020)
This study aims to determine and analyze the effect of user experience, perceived quality and perceived sacrifice on behavorial intention and customer satisfaction on the mobile gojek application in Palembang. Where the independent variables in this study are user experience, perceived quality and perceived sacrifice. While the dependent variables in this study are behavorial intention and customer satisfaction. The analysis used in this study used SEM with the lisrel 8.8 application. The SEM test results concluded that User Experience had no significant effect on Behavorial Intention and Customer Satisfaction. Whereas perceived quality and perceived sacrifice of a motorcycle taxi have a positive effect on behavorial intention or desire to use a motorcycle object and on customer satisfaction.